The renewal of the digital humanities. An overview of the transformation of professions in the humanities and social sciences - Marie-Laure Massot; Agnès Tricoche (Journal of Data Mining and Digital Humanities, 2021)
This article presents a study of the French-speaking digital humanities. It is based on the experience of two research engineers from the French National Center for Scientific Research (CNRS) who have been studying these issues for the last ten years. They conducted a survey at the École Normale Supérieure (ENS-Paris) which enabled them to draw up an overview of the transformation of the profession of humanities and social sciences research engineers in the context of the digital humanities. The Digit_Hum initiative, which they run in parallel with their respective activities at the ENS, also provided information for this overview thanks to its role as a space for discussion about the digital humanities along with training and structuring of this field at the ENS and the Université Paris Sciences & Lettres (PSL).